1998
DOI: 10.1111/j.1759-5436.1998.mp29004002.x
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Credit Programme Evaluation: A Critical Review

Abstract: summary Micro‐credit programmes have emerged as an antipoverty instrument in many low‐income countries. They target the poor, especially women, with financial services to help them become self‐employed in rural non‐farm activities of their choice. In contrast, micro‐credit programmes of the village banks supported by Accion International or Women's World Banking provide financial services in response to market failures in which formal financial institutions failed to cater financial services to small‐ and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 19 publications
(26 reference statements)
1
21
0
Order By: Relevance
“…The problem is equally present when there is inseparability of enterprises and household activities and behaviour in most of the poor households, and inseparability between micro Microfinance Programmes in Bangladesh 335 credit and informal and/or formal credit. Khandker (1998b) has candidly recognized the problem of fungibility in impact assessment. However, he argues that 'the close monitoring of group-based credit partly resolves the problem of fungibility'.…”
Section: Methodological Debate In Demand Side Analysis: What Do We Lementioning
confidence: 99%
“…The problem is equally present when there is inseparability of enterprises and household activities and behaviour in most of the poor households, and inseparability between micro Microfinance Programmes in Bangladesh 335 credit and informal and/or formal credit. Khandker (1998b) has candidly recognized the problem of fungibility in impact assessment. However, he argues that 'the close monitoring of group-based credit partly resolves the problem of fungibility'.…”
Section: Methodological Debate In Demand Side Analysis: What Do We Lementioning
confidence: 99%
“…While micro-credit literature stresses the need to alleviate poverty, the "empowerment" of women does not seem to include challenging the structural roots of poverty in addition to those of sexism (Khandker 1998;Mayoux 2000;Rogaly 1996). Although advocates and practitioners of micro-credit programs demonstrate a readiness to 1.…”
Section: Interlocking Oppressionsmentioning
confidence: 96%
“…A growing number of scholars, however, are sceptical of the impact of credit, in and of itself, on women's empowerment, and emphasize women's participation in lending-groups as having the greatest potential for empowerment. Beyond providing women with an escape from traditional social isolation, lending-groups are said to foster a gender based solidarity among women that transcends ethnic, class, and caste differences, thereby building a coalition that will enable women to effectively challenge structural and institutionalized gender oppression (Khandker 1998;Mayoux 2000;Rankin 2001). Proponents further claim that by providing women with an opportunity to interact with one another and articulate common interests and concerns, lending-groups expose women to new ideas and facilitate greater gender awareness.…”
Section: B2mentioning
confidence: 99%
“…As rightly noted by Bottomley (1971), if we are to identify a catalyst for a more productive combination of what is abundant supply of -under utilised‖ land and labour, that catalyst would be probably be cash. Also, Khandker (1998) observed that lack of savings and capital makes it difficult for many poor people to become self-employed and to undertake productive employment-generating. Consequently, the poor's productive base and contributions to the economy remain small, the production process is rudimentary and inefficient, growth is stifled and opportunities for links with the larger economy, particularly the forward linkages do not seem to exist.…”
Section: Introductionmentioning
confidence: 99%